Biomechanical comparison of vertebral augmentation and cement discoplasty for the treatment of symptomatic Schmorl's node: a finite element analysis. Issue 15 (31st October 2022) - Cai, Kaiwen; Zhang, Zhang; Luo, Kefeng; Cao, Feng; Lu, Bin; Wu, Yuanhua; Wang, Hongxia; Zhang, Kai; Jiang, Guoqiang
ABSTRACT: Percutaneous vertebral augmentation (PVA) and percutaneous cement discoplasty (PCD) are two relatively new minimally invasive surgeries for symptomatic Schmorl's reported in recent decade. However, the clinical evidence for the effectiveness of these two surgeries is insufficient. The purpose of this study was to compare the biomechanical benefits and risks of the two surgeries in order to analyze their biomechanical differences and effectiveness. We reconstructed Five lumbar finite element models via computed tomography data, including control model, PVA-ideal model, PVA-nonideal model, PCD-ideal model, and PCD-nonideal model. The stress and strain of Schmorl's nodes, bone marrow edema zone (BMEZ), affected endplate, and the overall stability of segment were analyzed and compared. The validity of our models was confirmed. As a result, the PVA-ideal model can significantly reduce the stress of Schmorl's node and the strain of BMEZ, while this effect is inappreciable in PVA-nonideal model. The PCD-ideal model significantly reduced the strain of Schmorl's nodes and BMEZ, and significantly improve segmental stability, but also resulted in a significant increase in the stress of Schmorl's nodes, BMEZ and endplates. The PCD-nonideal model not only lacks blocking effect, but also sharply increases the strain of Schmorl's nodes and BMEZ. Thus, We recommend that both PVA and PCD surgeries in ideal distribution facilitated a more stable paranodular biomechanical microenvironment. However, due to the possibility of poor biomechanical outcomes caused by the non-ideal cement distribution, the non-ideal distribution of bone cement needs to be remedied in practice.